Marketing Channel Problems of Herbal Medicines from the Perspective of Pharmaceutical Distribution Companies - Ali Abedini Abedini; Hamidreza Irani; Hamidreza yazdani (Tehran University of Medical Sciences, 2020)
Background and Aim: Due to the variety of herbal medicine products and brands, competition among herbal medicine manufacturing companies has become a scientific and tactical competition. Herbal medicine companies by identifying the problems of pharmaceutical distribution companies can evaluate them and find solutions to their problems and finally, they can maintain their competitive advantage in the market. Therefore, the purpose of this study was to identify the marketing channel problems of herbal medicine from the perspective of pharmaceutical distribution companies. Materials and Methods: In this research, with exploratory interviews, the marketing channel problems of herbal medicine were identified from the perspective of distributors and analyzed using content analysis method. The statistical population of this study was pharmaceutical distributor's managers in Tehran provinces, among which 16 persons were selected through the judgmental and snowball sampling method. Results: The results showed the marketing channel problems of herbal medicines were categorized in Product, Prices, Place, Promotion, Physical Evidence, Process and People. Conclusion: The government and the laws, in addition to the marketing can affect the marketing channel problems of these drugs from the perspective of distributors.